Association of serum vitamin C with liver fibrosis in adults with nonalcoholic fatty liver disease. (3rd July 2022) - Zhao, Yipu; Li, Hailu
Abstract: Objective: This study aimed to investigate the association between serum vitamin C and liver fibrosis in patients with NAFLD in the US adults. Methods: We conducted a cross-sectional analysis of data from the 2017 to 2018 cycle of National Health and Nutrition Examination Survey (NHANES). Serum vitamin C and transient elastography (TE)-accessed liver stiffness was taken as independent and dependent variables, respectively. Liver steatosis and fibrosis were detected by controlling attenuation parameter (CAP) and TE. NAFLD was defined by a CAP score of ≥248 dB/m without any indication of other causes of chronic liver disease. The median liver stiffness of ≥8.2 kPa was used to identify significant fibrosis (≥F2) among NAFLD patients. We calculated the adjusted odds ratio (OR) and 95% confidential intervals (CIs) for associations with significant NAFLD fibrosis using multivariable logistic regression models. Results: Overall, 1926 individuals with NAFLD were included in the analysis and 267 subjects met the definition of significant fibrosis. Serum vitamin C was associated with lower odds of liver fibrosis in NAFLD after adjusting for potential confounders (OR = 0.60, 95% CI, 0.43–0.84), while in the subgroup analysis stratified by gender and body mass index (BMI), this association showed a difference after adjusting for confounders (males: OR = 0.43, 95% CI, 0.26–0.71; females: OR = 0.78, 95% CI, 0.49–1.24). There were no significant associations of serum vitamin C with liver fibrosis in NAFLD with underweight or normal (OR = 1.34, 95% CI, 0.19–9.34). Conclusions: This cross-sectional study indicated an association of serum vitamin C with significant fibrosis in men and overweight or obese patients with NAFLD.